The Influence of Liquidity, Leverage, Profitability and Activity Against Growth of Profits at Property and Real Estate Companies Listed on BEI - Maulina Ratna Dewi, Siti Nurlaela & Kartika Hendra Titisari (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to test the influence of liquidity, leverage, profitability, andactivity against growth of profit at property and real estate companies listed onBEI.. The population of this research is all the property and real estate companieslisted in BEI during 2014-2016. Based on the method purposive sampling, samplesof this research as much as 34 property and real estate companies listed on BEI.Type of data used in this research is secondary data obtained from(www.idx.co.id). Methods of analysis used are multiple linear regression analysis.The results showed liquidity and leverage do not have influence to the profitgrowth, while profitability and activity have influence to the profit growth.Keywords: liquidity, leverage, profitability, activity, profit growth